Factorii care determină eficiența activității de aplicare a dreptului de către organele autorităților publice - Negru, Andrei; Manțuc, Elena (My University, 2011)
The efficiency of the state organs’ activity greatly depends on the efficiency of the act itself of apply- ing law in the process of taking decisions, namely on the impact of this act upon the regulated social relations. The activity of state organs is a personalized one, being exercised by definite subjects, named agents of the state power and this is why we talk about a great number of factors and conditions that influence the quality and efficiency of the applying law activity. The investigation carried out in this paper demonstrates once more that it is impossible to analyse exclusively from a juridical expectation the factors and conditions that determine the quality and efficiency of the mentioned activity, being necessary to study them from the sociological and psychological point of view, too. So, besides such conditions as the quality of national legislation, the correct and legal system of administration, the level of civil servants professionalism, the author underlines the major importance of the civil ser- vants’ level of juridical culture. When the level of juridical culture and conscience of the civil servants corresponds to a minimal satisfactory level for the detained function, it becomes real to talk about the presumption of their impartiality and integrity in the law applying process, by improving legal, coherent and scientifically based decisional mechanisms. The paper corollary is based on the idea of the professional ethics of the civil servants, on their moral characteristics and system of values. For ensuring the efficiency of the activity of applying law by the organs of the state power, first of all, there must be created functional conditions to prevent actions and decisions based on individual interest and to stimulate legal, well-considered and consciously assumed decisions.